Breast fillers on the rise: a silent epidemic of unregulated aesthetic trend - Hassan, Radhiana; Ab Mumin, Nazimah (IIUM Press, 2026)
The use of breast fillers for aesthetic enhancement is gaining popularity over the past decade, driven by social media influence, accessibility, and the perception of minimal invasiveness. However, unlike approved breast implants, many injectable breast fillers remain unregulated and often administered by unqualified personnel in non-medical settings. This growing trend is accompanied by a striking lack of public awareness regarding its potential complications. Reported complications range from localized inflammatory reactions, granuloma formation, chronic pain, and infection to devastating sequelae such as tissue necrosis, migration of filler material, breast deformity, and systemic embolic phenomena. Breast fillers also cause profound difficulties to routine breast cancer surveillance and diagnosis. These complications often results in substantial physical, psychological and socioeconomic burden to affected individuals. This article highlights the emerging public health concerns surrounding the use of unregulated breast fillers, emphasizing the gap between increasing popularity and insufficient patient education on safety and long-term consequences. Thus, greater regulatory enforcement, improved public awareness, and multidisciplinary collaboration between clinicians, radiologists, and policymakers are urgently needed to curb these unsafe practices, in order to safeguard patient welfare in the era of rapidly expanding aesthetic medicine.